Conviction, Conversion, Commitment A study on the religious personality of St Paul - Pathrapankal, Joseph (Journal of Dharma, 1987)
"I was circumcised when I was a week old. I am an Israelite by birth, of the tribe of Benjamin, a pure-blooded Hebrew. As far as keeping the Jewish Law is concerned, I was a Pharisee, and I was so zealous that I persecuted the Church. As far as a person can be righteous by obeying the commands of the Law, I was without fault. But all those things that I might count as profit, I now reckon as loss for Christ’s sake. Not only those things; I reckon everything as complete loss for the sake of what is so much more valuable, the knowledge of Christ Jesus my Lord. For his sake I have thrown everything away; I consider it all as mere refuse, so that I may gain Christ and be completely united with him. ....All I want is to know Christ and to experience the power of his resurrection, to share in his sufferings and become like him in his death, in the hope that I myself will be raised from death to life" (Phil 3 :5-11).